(3GdYhdeI hJCKjQGJgG Ydi GdLgGR GdeUQaj (B:s (3GdLRA GdChd (B/s - (3NfahSj, YHO GdYRjRs ((3YeGf (B: s (3OGQ GdCjGe ddfTQ hGdJhRjY(B, s, 2016)
(3jVe GdYhdeI hGdefXheI GdbGfhfjI ddLgGR GdeUQaj GdLRGFQj, JMQjQ Shb GdbQV hab bhGYO GdYQV hGdWdH, GJLGgGJ EUdGM GdfXGe GdeUQaj HYO (B1990(3, JRhjO Shb GdbQV HGdVeGfGJ GdeUQajI GdMOjKI(B.s
(3HjHdjhZQGajG(B: (3U U(B395-427s
Keywords: (3GdHfhcs; (3GdHfhc(B- (3GdMSGHGJ GdeUQajI s; (3GdbWGY GdNGUs